Psychological factors affecting young people's environmental responsibility: evidence from public university students - Muhammad Naimulah Aziz,; Muhammad Iqmal Syamier Khairulnizam,; Nurul Hidayana Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Young people are recognized for their role in achieving the Sustainable Development Goals. The main advantage these young people have is their ability to use new media, think creatively, and care for the environment. Most youth still need to learn about environmental issues and their effects, and lack of funds, support, and guidance can restrict their ability to leave a practical impact on environmental conservation. This study examines the level of pro-environmental behavior among university students in Universiti Teknologi MARA (UiTM), Malaysia. The research data was obtained quantitatively through a questionnaire. The questionnaire has been distributed to 300 respondents. This study employed a multistage random sampling technique by first clustering the sample into three branches, namely Negeri Sembilan, Shah Alam, and Puncak Alam. Second is a convenience sampling technique. Underlying the concept of dispositional attribution, this study investigated relationships between commitment, green lifestyle, environment consciousness, green self-efficacy, and pro-environmental behavior. Results found that pro-environmental behavior is at a high level. Next, findings show a significant correlation between enablers and pro-environmental behavior. Study regression results also show that environmental commitment is the most significant predictor of pro-environmental behavior. Theoretically, this study has contributed new insights to the current literature on environmental management and studies by highlighting internal and external attribution that could affect pro-environmental behavior. As an implication, the application of environmental commitment needs to be revealed in the early stage. The youth, who are also future heirs, must be exposed to green skills to increase their understanding of the importance of environmental conservation.